Pelatihan Aplikasi Pengelolaan Keuangan Praktis bagi Pelaku UMKM di Kabupaten Pringsewu Propinsi Lampung - Citrawati Jatiningrum; Eka Ridhawati; Novi Ayu Kristiana Dewi; Marilin Kristina; Reni Astika (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2023)
- SMEs currently has growth rapidly and required follow development of information technology to support the effectiveness and efficiency their business. Financial management is something that is often ignored by SMEs, whereas financial management greatly influences the business that is being run. This community service activity aims to provide coaching for SMEs in utilizing digitalization-based financial management applications. This training was attended by several SMEs in Pringsewu Regency. The method used in this service activity is a training method on the use of information technology in management. The result of this activity is that SMEs business actors have the skills to manage finances and use digital-based SME financial applications. This activity also shows that the majority of SMEs business actors are capable of implementing financial transaction recording. SMEs realize that financial reporting is important to support business effectiveness and is a component for developing business through business credit for SMEs